Understanding the Entrepreneurial Mind 2009
DOI: 10.1007/978-1-4419-0443-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Efficacy, Control, and Risk: A Theory of Mixed Control

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 110 publications
(167 reference statements)
3
34
0
Order By: Relevance
“…Moreover, Monsen and Urbig [27] state that the evaluation of entrepreneurial opportunity depends on the perception of self-eicacy perception, corroborating our indings. Apart from cognition, it is evident that new value creation activities are related to radical innovation in a way that creates new legitimacy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, Monsen and Urbig [27] state that the evaluation of entrepreneurial opportunity depends on the perception of self-eicacy perception, corroborating our indings. Apart from cognition, it is evident that new value creation activities are related to radical innovation in a way that creates new legitimacy.…”
Section: Discussionsupporting
confidence: 88%
“…Optimism in relation to value creation is complicated by the fact that those with high levels of optimism may perceive less risk in potential opportunities, thereby leading to possible failure [27]. However, in our research sample, all entrepreneurs demonstrated success in changing value proposition in the market.…”
Section: Optimismmentioning
confidence: 79%
See 2 more Smart Citations
“…Accordingly, the family business context and hence the external source of entrepreneurial efficacy adds to the perceived self-efficacy to take risks and pursue an entrepreneurial career. Building on Monsen and Urbig (2009) we thus propose that the inclination to start an own firm for students with family business background is π = (e s + e f ), with e s and e f representing self-and family-induced efficacy beliefs. In stark contrast to above motivation, the same external context may reduce the inclination to start an own firm through lessening perceptions of internal locus of control when pursuing such a career (π = (c s − c f ), with c s and c f representing self-and family-induced control beliefs).…”
Section: Discussionmentioning
confidence: 99%